(3eUMa TQjas
(3ChdgG (B:s
(3aGJMI ddcJGH Ke ShQI GdHbQI s
(3BNQgG (B:s
(3ShQI GdCfYGe hQaY HYVce ahb HYV OQLGJ djHdhce Ef QHc SQjY GdYbGH hEfg dZahQ QMje s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B/ (3GdeZQH (B(1330 (3O(B) s
Keywords: (3GdcJH GdSeGhjIs